Internal and external networking behavior: An investigation of relationships with affective, continuance, and normative commitment. Issue 5 (2nd September 2014) - Y. McCallum, Shelly; L. Forret, Monica; Wolff, Hans-Georg
Abstract : Purpose: – The purpose of this paper is to examine the relationships of internal and external networking behaviors of managers and professionals with their affective, continuance, and normative commitment. Design/methodology/approach: – Data were obtained from 335 managers and professionals of a health system who completed a survey on networking behavior and organizational commitment. Correlation analyses and multiple regressions were performed to test our hypotheses. Findings: – The results showed that networking behavior focussed within an individual's organization was positively related with affective commitment and normative commitment. Networking with individuals outside of an individual's organization showed a significant negative relationship with normative commitment. Contrary to expectations, networking externally was not related to affective commitment, and neither internal nor external networking behaviors were related to continuance commitment. Research limitations/implications: – Because data were collected at a single point in time, no statements can be made about causality. Future research is needed assessing both internal and external networking behavior and the three types of organizational commitment across time to help determine direction of causality or whether reciprocal relationships exist. Practical implications: – Organizations that encourage internal networking behaviors may see individuals who are more connected with their colleagues and affectively committed to their organizations. However, encouraging external networking behavior may result in a drop in normative commitment as individuals might identify more with their profession than their employer. Originality/value: – Although previous research has shown that networking behavior is related to job performance and career success measures, the research extends the literature by investigating whether networking is related to attitudinal variables such as organizational commitment. The paper explores whether differential relationships exist between internal and external networking behavior with three types of organizational commitment.